PENGARUH TEMAN SEBAYA TERHADAP HASIL BELAJAR PENGOLAHAN DAN PENYAJIAN MAKANAN INDONESIA PADA SISWA SMK - Rinny Julianty (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
This research investigates the influence of peers in their study result in making and serving Indonesian foods, peers, and the study result of making and serving indonesian foods. This study is ex-post facto research and sample research used Isaac and Michael. The sample was from 51 students. Data collection procedure used questionnaire and documentation method. The validity used correlation Product Moment and the reliability used Cronbach’s Alpha. Data techniques analysis used descriptive analysis and hypothesis test used Product Moment which began with normaly and linieritas test. The result of this study; positive influence of peers in their study result in making and serving Indonesian foods and the contribution of peers of their study result in making and serving Indonesian foods were 22,1%, and the rest 77,9% was influenced by other factors; peers was in sufficient category; and the result of making and serving Indonesian foods was in the sufficient category. Key words: Peers, Study Result